Aqueous two-polymer phase extraction of single-wall carbon nanotubes using surfactants. Issue 9 (15th July 2019) - Fagan, Jeffrey A.
Abstract : Aqueous two-polymer phase extraction is described for its best-practice use to isolate single-wall carbon nanotube species. Abstract : This review details the current state of the art in aqueous two-phase extraction (ATPE) based separations of surfactant dispersed single-wall carbon nanotubes by their chemical species, i.e., (n, m) structure, semiconducting or metallic nature, and enantiomeric handedness. Discussions of the factors affecting each separation, including workflow effects, variations of different surfactant and nanotube materials, and the underlying physical mechanism are presented. Lastly an outlook on the applications of ATPE at bench scale and implementation to larger scales is discussed, along with identification of research directions that could further support ATPE development.